The Refugee in International Law - Goodwin-Gill, Guy S.; McAdam, Jane (Oxford University Press, 2021)
"The status of the refugee in international law, and of everyone entitled to protection, has ever been precarious, not least in times of heightened and heated debate: people have always moved in search of safety, and they always will. In this completely revised and updated edition, the authors cast new light on the refugee definition, the meaning of persecution, including with regard to gender and sexual orientation, and the protection due to refugees and those affected by statelessness or disasters. They review the fundamental principle of non-refoulement as a restraint on the conduct of States, even as States themselves seek new ways to prevent the arrival of those in search of refuge. "